Evaluation of solvents based on ionic liquids for deterpenation - Jorge, Catarina Daniela Santos (2018)
Essential oils are part of our lives in many different ways, being used directly or after separation into their components or fractions. Pharmaceutical and chemical industries are some examples of industries that use the pure components of essential oils while food industry normally uses the soluble fraction. Deterpenation is the separation process into the fraction rich in monoterpenes and the fraction rich in oxygenated compounds. Over the years, different methods and technologies were developed and studied to deterpenate essential oils. In this work, the use of ionic liquids as separation agents in the extraction of limonene and linalool, the representatives terpenes of citrus essential oil, was evaluated. To improve the capacity of the extraction, DEGDME was used as a co-extractant. Since there are millions of possible ionic liquids, initially a preselection was done with the use of the predictive tool COSMO-RS. Based on the selectivities, some ionic liquids with potential for the separation were selected for further investigation. The same was done for the co-extractant selection; however the calculations were based on the miscibility with the terpenes. Several ternary mixtures constituted by limonene, linalool, DEGDME and the ionic liquids composed of the cations 1-ethyl-3- methylimidazolium and 1-butyl-3-methylimidazolium and the anions acetate, hydrogensulfate, methylsulfate and methanesulfonate as anions were studied experimentally. The quantification of the mixtures was performed using nuclear magnetic resonance (NMR) analysis. Most of the results are accordingly to COSMO-RS predictions validating this model for the selection of ionic liquids for the deterpenation process. The results show that 1-butyl-3- methylimidazolium hydrogensulfate is the best ionic liquid for this separation.